2022
DOI: 10.1155/2022/1563731
|View full text |Cite|
|
Sign up to set email alerts
|

English-Chinese Machine Translation Based on Transfer Learning and Chinese-English Corpus

Abstract: This paper proposes an English-Chinese machine translation research method based on transfer learning. First, it expounds the theory of neural machine translation and transfer learning and related technologies. Neural machine translation is discussed, the advantages and disadvantages of various models are introduced, and the transformer neural machine translation model framework is selected. For low-resource Chinese-English parallel corpus and Tibetan-Chinese parallel corpus, 30 million Chinese-English paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the literature on teaching English to Chinese translation, a number of study projects were suggested; a few recent works are reviewed here, Xu [21] have suggested that a transfer learning-based English-Chinese machine translation study methodology. It begins by outlining the principles of transfer learning, neural machine translation and related fields of study.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature on teaching English to Chinese translation, a number of study projects were suggested; a few recent works are reviewed here, Xu [21] have suggested that a transfer learning-based English-Chinese machine translation study methodology. It begins by outlining the principles of transfer learning, neural machine translation and related fields of study.…”
Section: Methodsmentioning
confidence: 99%
“…Parallel corpora are usually used in corpus translation studies. Parallel corpora aid in comprehending and analyzing translated texts, particularly in machine translation models that use sufficient training data (Xu, 2022;Zhai et al, 2020). By comparing the grammatical parallels and contrasts in a corpus of six translated texts, the translators' styles can be discovered (Wang, 2023;Wang & Wang, 2022).…”
Section: Parallel Corpusmentioning
confidence: 99%
“…This technological innovation not only enhances accessibility and inclusivity in diverse linguistic settings but also promotes global collaboration and understanding. Moreover, the continuous refinement and improvement of such systems signify a promising trajectory towards more effective and nuanced bilingual communication in an increasingly interconnected world [5].…”
Section: Introductionmentioning
confidence: 99%